PEMBANGUNAN PENDIDIKAN KARAKTER DALAM NUANSA BAHASA - Kartikasari, Ernadewi (UNIVERSITAS SLAMET RIYADI, 2014)
The aim of this study is to describe the developing of character education in the nuances of language. The methode used in this study is qualitative descriptive. Character education is a planned effort so that it cannot be instantly accepted and understood. In developing character education, language is expected to contribute useful influence and to improve students' acheivement.